MOLECULAR DETECTION OF PROSTATE CANCER USING A PANEL OF DNA METHYLATION BIOMARKERS - Raluca, Dumache; Maria, Puiu; Dana, David; Serban, Negru; Victor, Dumitrascu (European Scientific Journal, ESJ, 2013)
Introduction: The diagnostic of prostate cancer (PCa) using serumbased prostate specific antigen (PSA) has some limitations due to falsepositive and negative results. The purpose of our study was to analyse the hypermethylation of three genes from plasma samples and to determine the feasibility of these genes to aid as biomarkers in detecting PCa in plasma by noninvasive methods. Materials and Methods: Genomic DNA was extracted from the peripheral blood plasma of 74 patients with localized PCa. All the samples were examined for aberrant hypermethylation in retinoic acid receptor β variant 2 (RARβ2), glutathione S-transferase P1 (GSTP1) and Ras association domain family 1 isoform A(RASSF1A) genes, using methylation-specific PCR (MSP), and the results were correlated with the clinicopathological parameters. Results: The percent of methylation of the analyzed genes was as follows: RARβ2 was found methylated in 54 cases (73 %), GSTP1 in 58 cases (78.4%), and RASSF1A was found methylated in all 74 cases (100%). Conclusion: Our study demonstrates that, using a panel of DNA methylated biomarkers aids the identification of PCa patients and with minimally invasive techniques , may yield information independent of serum PSA or the TNM stage.